1993
DOI: 10.1063/1.353212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anneal ambients and Pt thickness on Pt/Ti and Pt/Ti/TiN interfacial reactions

Abstract: Using x-ray diffraction, Rutherford backscattering spectrometry, Auger electron spectroscopy, and scanning electron microscopy, effects of ambient anneal and Pt thickness on the interdiffusion of Pt/Ti bilayers deposited on SiO2/Si and on reactively sputtered TiN/Ti/Si substrates have been investigated. The Pt layer was 2000 or 930 Å thick while the Ti thickness was fixed at 1000 Å. The wafers were annealed in either O2 or N2 ambients or in N2 followed by O2, with temperatures ranging from 600 to 800 °C for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(39 citation statements)
references
References 26 publications
4
33
1
Order By: Relevance
“…Titanium diffuses through the Pt, which is consistent with electrode material studies by J.O. Olowolafe et al [139] and by A. Erlich et al [140]. Titanium diffused through the Pt and formed a TiO 2 dead layer with a lower dielectric constant than BST.…”
Section: Silicon Substratesupporting
confidence: 78%
See 2 more Smart Citations
“…Titanium diffuses through the Pt, which is consistent with electrode material studies by J.O. Olowolafe et al [139] and by A. Erlich et al [140]. Titanium diffused through the Pt and formed a TiO 2 dead layer with a lower dielectric constant than BST.…”
Section: Silicon Substratesupporting
confidence: 78%
“…CHARACTERIZATION AND OPTIMIZATION Therefore, glass-planarized alumina and thermally oxidized silicon require an adhesion layer to prevent delamination from the substrate [83]. The most commonly used adhesion layer consists of titanium (Ti) [32,137,139,140].…”
Section: Metal Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pt hillocks with radii typically ranging from 20 to 70 nm for the case at hand are much smaller than those on Pt/ Ti electrode stacks as reported earlier. [8][9][10] For Pt films deposited using dc sputtering at low temperatures, a compressive stress is generally present. 10,[18][19][20] The stress is relaxed under high-temperature treatments through the formation of Pt hillocks and becomes tensile upon cooling down to room temperature because of the thermal strain.…”
Section: A Formation Of Pt Hillocks On the Bare Pt Electrodementioning
confidence: 99%
“…However, the Pt/ Ti metallic electrode shows poor thermal stability and reliability including the formation of Pt hillocks [5][6][7][8] or bumps under thermal conditions, 9 surface morphology evolution during aging, 7 short circuit of ferroelectric capacitors caused by the Pt hillocks, 10 severe diffusion of Ti into Pt, and even encapsulation of Pt hillocks with TiO x during annealing. 6,[9][10][11] In contrast, Sreenivas et al reported that the Pt/ TiO x electrode structure shows an improved thermal stability. 6 For a given ferroelectric medium with a certain chemistry and structure, the ferroelectricity is dependent on the electrical and mechanical boundary conditions to a great extent.…”
Section: Introductionmentioning
confidence: 99%